Factors influencing job satisfaction among tourism and hospitality undergraduate students: A path to a sustainable tourism industry in Bangladesh - Sukrana, Bipasha; Jui, Farjana Islam; Khan, Noor Hasan Mahmud (Journal of Sustainable Tourism and Entrepreneurship, 2025)
Purpose: The tourism industry in Bangladesh presents a promising avenue for economic expansion and employment generation. Many undergraduate students in Bangladesh work part-time or full-time in this field while studying. This study aims to explore the factors that determine the job satisfaction of these tourism and hospitality undergraduate students, addressing a gap in existing research. Research Methodology: A convenience sample of 118 undergraduate students from five universities was surveyed using a structured questionnaire. The data were analyzed using SPSS 25, and multiple linear regression analysis was employed to assess the impact of various factors on job satisfaction. Results: The findings reveal that compensation and benefits, communication, opportunities for growth, and the nature of the work significantly influence job satisfaction, whereas work environment and company policy have a comparatively weaker association. Limitations: The small sample size and the use of a non-probability sampling method have limited the generalizability of the present study, which may not fully represent the broader student workforce in the tourism sector. Contribution: This research provides actionable insights for industry leaders and HR professionals in the tourism and hospitality sector, helping them to better understand and enhance job satisfaction among student employees. Novelty: This is the first comprehensive study to investigate the determinants of job satisfaction among tourism and hospitality undergraduate students in Bangladesh who are currently engaged in academic studies and employment.